Reflection on the Trend of Data Property Rights in China - Ruichen Zhang (Law and Economy, 2023)
In the digital age, traditional legal paradigms are facing challenges. The swift advancement of technology has given rise to numerous novel challenges. This article intends to elucidate the true essence of data property rights in the context of the interaction between law and technology, reflect upon the origins of the rise of property rights in China, and engage in a multi-faceted exploration from the perspectives of judicial practice, theoretical foundations, and the field of law and economics. In conclusion, we should prudently apply legal norms to new changes, and the resolution of issues and the establishment of a well-functioning market should not rely solely on the construction of digital property rights.